OPTIMALISASI MANAJEMEN PENGELOLAAN SAMPAH BERBASIS KOMUNITAS DI PERUMAHAN KASONGAN PERMAI KABUPATEN BANTUL - Arsanti, Vidyana; Nur Rahmahwati, Isti; Sukma Kharisma, Rizqi; Ihsan Fajruna, Muhammad; Mariady Loudewyk De Janero, Miguel (Universitas Mataram, 2025)
The closure of the Piyungan landfill has forced waste management to be carried out independently by communities in each region, especially the Special Region of Yogyakarta, which has the smallest scope, namely the village. One of the villages in Bantul has carried out community-based waste management. However, support is needed through community service activities to optimize waste management, which is referred to as “Booster”. The location of community service activities is in Kasongan Permai Housing. This activity aims to boost more optimal waste management and increase community independence in managing waste. The method used in this community service activity is the socialization of the community partnership program by the service team so that the community is interested in managing waste, making a participatory community-based waste management flow through Forum Group discussion, making a map of the waste management area and training community empowerment in managing waste through material presentation by the service team and mini practice of processing waste by partners with the service team. The results of this activity include: (1) a clear waste management flow map so that the division of tasks in waste management becomes clearer; (2) increased understanding and community independence related to waste management by 15% or N-Gain 0.6, which means moderate. The conclusion is that there is a precise waste management flow and plan map, optimal waste management, and increased community understanding and independence. Both will optimize community-based waste management.